Hepatoprotective and cardioprotective effects of empagliflozin in spontaneously hypertensive rats fed a high-fat diet - Hojná, Silvie; Malínská, Hana; Hüttl, Martina; Vaňourková, Zdeňka; Marková, Irena; Miklánková, Denisa; Hrdlička, Jaroslav; Papoušek, František; Neckář, Jan; Kujal, Petr; Behuliak, Michal; Rauchová, Hana; et al. (Biomedicine & pharmacotherapy, 2024)
A combination of liver and heart dysfunction worsens the prognosis of human survival. The aim of this study was to investigate whether empagliflozin (a sodium-glucose transporter-2 inhibitor) has beneficial effects not only on cardiac and renal function but also on hepatic function. Adult (6-month-old) male spontaneously hypertensive rats (SHR) were fed a high-fat diet (60% fat) for four months to induce hepatic steatosis and mild heart failure. For the last two months, the rats were treated with empagliflozin (empa, 10 mg.kg-1.day-1 in the drinking water). Renal function and oral glucose tolerance test were analyzed in control (n=8), high-fat diet (SHR+HF, n=10), and empagliflozin-treated (SHR+HF+empa, n=9) SHR throughout the study. Metabolic parameters and echocardiography were evaluated at the end of the experiment. High-fat diet feeding increased body weight and visceral adiposity, liver triglyceride and cholesterol concentrations, and worsened glucose tolerance. Although the high-fat diet did not affect renal function, it significantly worsened cardiac function in a subset of SHR rats. Empagliflozin reduced body weight gain but not visceral fat deposition. It also improved glucose sensitivity and several metabolic parameters (plasma insulin, uric acid, and HDL cholesterol). In the liver, empagliflozin reduced ectopic lipid accumulation, lipoperoxidation, inflammation and pro-inflammatory HETEs, while increasing anti-inflammatory EETs. In addition, empagliflozin improved cardiac function (systolic, diastolic and pumping) independent of blood pressure. The results of our study suggest that hepatoprotection plays a decisive role in the beneficial effects of empagliflozin in preventing the progression of cardiac dysfunction induced by high-fat diet feeding.
Keywords: Liver; Animals; Kidney; Sodium-Glucose Transporter 2 Inhibitors; hypertenze; Glucosides; kardiotonika; játra; Fatty Liver; glukosidy; benzhydrylové sloučeniny; Diet, High-Fat; Blood Glucose; ztučnělá játra; Protective Agents; Rats, Inbred SHR; krevní tlak; Benzhydryl Compounds; Hypertension; Male; krysa rodu Rattus; Cardiotonic Agents; potkani inbrední SHR; mužské pohlaví; zvířata; ochranné látky; Blood Pressure; ledviny; dieta s vysokým obsahem tuků; krevní glukóza; Rats; glifloziny